2013
DOI: 10.1039/c3cc47090c
|View full text |Cite
|
Sign up to set email alerts
|

2-Iodoxybenzoic acid organosulfonates: preparation, X-ray structure and reactivity of new, powerful hypervalent iodine(v) oxidants

Abstract: New powerful hypervalent iodine(V) oxidants, tosylate and mesylate derivatives of 2-iodoxybenzoic acid (IBX), were prepared by the reaction of IBX with the corresponding sulfonic acids. Single crystal X-ray crystallography of the diacetate derivative of IBX-tosylate revealed an unusual heptacoordinated iodine geometry without any significant intermolecular secondary interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…For comparison, the oxidation of HFIP with IBX-tosylate at 60 o C proceeds with only 60% conversion after 7 hours. 16 The oxidation of higher polyfluorinated alcohols 11 can be conveniently performed using IBX-ditriflate generated in situ from IBX and triflic acid in dichloromethane. Polyfluoroaldehydes resulting from these oxidations were isolated after aqueous work-up in the form of gem-diols 12-15 in high yields (Scheme 2).…”
Section: O2mentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, the oxidation of HFIP with IBX-tosylate at 60 o C proceeds with only 60% conversion after 7 hours. 16 The oxidation of higher polyfluorinated alcohols 11 can be conveniently performed using IBX-ditriflate generated in situ from IBX and triflic acid in dichloromethane. Polyfluoroaldehydes resulting from these oxidations were isolated after aqueous work-up in the form of gem-diols 12-15 in high yields (Scheme 2).…”
Section: O2mentioning
confidence: 99%
“…In a search for the more powerful iodine(V) oxidants, several IBX modifications have been synthesized and investigated. [12][13][14][15][16] The most notable powerful iodine(V) oxidants are represented by the highly electrophilic IBX-tosylate and IBX-OTs diacetate 3, 16 which show high reactivity in the oxidation of structurally complex primary and secondary alcohols. 17 In the present communication, we want to report the preparation, structure and reactivity of IBX-ditriflate 4, the most powerful oxidant in the series of structurally similar IBX derivatives ( Fig.…”
mentioning
confidence: 99%
“…The solvent was distilled off, the residue was ground with hexane, and the solvent decanted. 3 of 12 1001 w, 1024 m, 1135 s, 1176 s, 1195 s, 1267 m, 1342 vs, 1367 s, 1388 s, 1436 vs, 1558 s, 1591 w, 1627 w, 1687 w, 2613 w, 2861 m, 2941 m, 2991 m, 3062 m, This compound was prepared by treating 2-iodoxybenzoic acid (IBX) with p-TsOH•H 2 O in acetic anhydride according to a published procedure [15]. A mixture of IBX (2.73 g, 9.75 mmol), p-TsOH•H 2 O (5.55 g, 29.25 mmol, 3.0 equiv), and acetic anhydride (37.5 mL) was stirred at room temperature.…”
Section: General Proceduresmentioning
confidence: 99%
“…Recently, we have reported the preparation and structural study of new tosylate derivatives of IBX, namely, the tosylate derivative of DMP (DMP-OTs, 2) and the tosylate derivative of IBX (IBX-OTs, 3). 4 These compounds are prepared by simple treatment of IBX (1) with TsOH•H 2 O in acetic anhydride at room temperature (Scheme 1). Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies [4] have shown that tosylate 3 has a higher reactivity toward alcohols compared with IBX or DMP. In particular, we have found that the oxidation of simple primary alcohols (1-octanol and substituted benzyl alcohols) with 1 equiv of IBX-OTs 3 in general is complete within 3-10 min at room temperature with a quantitative conversion to the respective carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%